Three essays of corporate finance - Cha, Yun Ju (Nanyang Technological University, 2021)
My dissertation aims at understanding various aspects of corporate finance. It contains three chapters. The first chapter examine the profitability of insider trading by large non-family individual shareholders (LISs), the sources of their profits, and the informativeness of their trading in predicting firms’ future. We find that LISs earn higher abnormal profits from their purchase (sales) transactions than other insiders, particularly when their firms have poorer governance, lower litigation risk, and higher information asymmetry and when they engage in opportunistic trades. LISs’ trading profits are greater when they are older and better educated, reside in local areas, and have more experience. We further find that LIS’s net purchases are positively associated with firms’ future performance. In the second chapter, we examine whether trust of the acquirer (target) country’s citizens towards the target (acquirer) country’s citizens (Acquirer’ (Target’s) generalized trust)) affects the valuation effects of cross-border mergers and acquisitions (M&As). We find that acquirers with higher Acquirer’s (Target’s) generalized trust realize higher announcement returns and have better post-M&A long-term operating and stock performance than those with lower Acquirer’s (Target’s) generalized trust. These acquirers also lay off fewer employees after M&As. An increase in post-merger stock performance is particularly evident when M&A partners face difficulties in achieving the post-M&A integration, such as linguistic and cultural differences, and geographic distance. The third chapter examine the effect of large non-family individual shareholders (LISs) on firm value. We find that firms with LISs have higher firm value than those without LISs, particularly when LISs’ ownership is larger and when firms have poor governance. Further analyses show that firms with LISs have higher CEO incentive pay and CEO turnover-performance sensitivity but lower investment and stock return volatility. These results support that the LISs enhance firm value by performing active monitoring and thus reducing managerial agency problems.